2005
DOI: 10.1051/0004-6361:200500111
|View full text |Cite
|
Sign up to set email alerts
|

A companion to AB Pic at the planet/brown dwarf boundary

Abstract: Abstract. We report deep imaging observations of the young, nearby star AB Pic, a member of the large Tucana-Horologium association. We have detected a faint, red source 5.5 South of the star with JHK colors compatible with that of a young substellar L dwarf. Follow-up observations at two additional epochs confirm, with a confidence level of 4.7σ, that the faint red object is a companion to AB Pic rather than it being a stationary background object. A low resolution K-band spectrum indicates an early-L spectra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
213
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(228 citation statements)
references
References 33 publications
14
213
0
1
Order By: Relevance
“…As of today nine exoplanetary systems have been directly imaged in the optical or near-infrared band, but only five of them are still embedded: GQ Lup (Neuhäuser et al 2005) and CT Cha (Schmidt et al 2008), but they are rather hosting a stellar companion as the companion masses are, because high as 21.5 M J and 17 M J , respectively; 2M1207 (Chauvin et al 2004(Chauvin et al , 2005a) hosting a 4 M J mass planet; UScoCTIO 108 (Kashyap et al 2008) hosting a 14 M J mass planet; β Pic (Lagrange et al 2009a,b) hosting an 8 M J mass planet. AB Pic (Chauvin et al 2005b), HR 8799 (Marois et al 2008) (triple system), SR 1845 (Biller et al 2006) and Fomalhaut (Kalas et al 2008) are mature planetary systems with ages of about 30 Myr, 60 Myr, 100 Myr, and 200 Myr. Note that centimeter wavelength radio observations of a very young (<0.1 Myr) disk around HL Tau, presented by Greaves et al (2008), revealed the possibility of a 12 Jupiter mass giant planet being in formation at ∼75 AU.…”
Section: Introductionmentioning
confidence: 99%
“…As of today nine exoplanetary systems have been directly imaged in the optical or near-infrared band, but only five of them are still embedded: GQ Lup (Neuhäuser et al 2005) and CT Cha (Schmidt et al 2008), but they are rather hosting a stellar companion as the companion masses are, because high as 21.5 M J and 17 M J , respectively; 2M1207 (Chauvin et al 2004(Chauvin et al , 2005a) hosting a 4 M J mass planet; UScoCTIO 108 (Kashyap et al 2008) hosting a 14 M J mass planet; β Pic (Lagrange et al 2009a,b) hosting an 8 M J mass planet. AB Pic (Chauvin et al 2005b), HR 8799 (Marois et al 2008) (triple system), SR 1845 (Biller et al 2006) and Fomalhaut (Kalas et al 2008) are mature planetary systems with ages of about 30 Myr, 60 Myr, 100 Myr, and 200 Myr. Note that centimeter wavelength radio observations of a very young (<0.1 Myr) disk around HL Tau, presented by Greaves et al (2008), revealed the possibility of a 12 Jupiter mass giant planet being in formation at ∼75 AU.…”
Section: Introductionmentioning
confidence: 99%
“…Known systems with a star similar to the Sun and a planet in an orbit with large a semimajor axis are: GQ Lup (M = 0.8 ± 0.2 M , Seperuelo et al 2008; a P ≈ 100 AU, Neuhäuser et al 2005), 1RXS J160929.1-210524 (M = 0.85 +0.20 −0.10 M ; a P ≈ 330 AU, Lafreniere et al 2008). Also AB Pic has a planet candidate at a separation of ≈258 AU (Chauvin et al 2005). But AB Pic is classified as a dwarf star, similar to many known systems with large semimajor axes.…”
Section: Discussionmentioning
confidence: 99%
“…It is a probable member of the Tucana-Horologium association with an age of 10-50 Myrs. AB Pic b is a ∼13 M Jupiter mass object at the planet/BD boundary (Chauvin et al 2005b) and separation of 275 AU. It is also member of the Tucana-Horologium association.…”
Section: Datasetmentioning
confidence: 99%
“…Other than a few planets (e.g., Kuzuhara et al 2013;Rameau et al 2013b) and brown dwarfs (BDs; e.g., Chauvin et al 2005b;Biller et al 2010;Mugrauer et al 2010;Wahhaj et al 2011;Carson et al 2013) detected, many surveys found no planetary companions. The null results cannot be used to fit power-laws to the planetary distributions beyond 10 AU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation